Pengaruh Stress Kerja, Lingkungan Kerja dan Kepuasan Kerja terhadap Produktivitas Kerja Pegawai selama Pandemi Covid-19 (Studi Kasus di Kantor Kecamatan Megamendung) - Anggita Amalia (2021)
This research is a quantitative study with the aims of testing and knowing the effect of Job Stress, Work Environment and Job Satisfaction on Employee Work Productivity at the Megamendung District Office during the Covid-19 Pandemic. This study uses a sample size of 43 respondents who are all employees of the Megamendung District Office. The analytical technique used in this research is the Coefficient of Determination Test, T Test (Partial) and F Test (Simultaneous) using Smart PLS 3.0 software. The test results show that (1) Job Stress has a significant effect on Employee Work Productivity at the Megamendung District Office, (2) the Work Environment has a significant effect on Employee Work Productivity at the Megamendung District Office, (3) Job Satisfaction has no significant effect on Employee Work Productivity in the Office Megamendung District and (3) Job Stress, Work Environment and Job Satisfaction have a significant effect together on Employee Work Productivity at the Megamendung District Office. Keywords: Job Stress, Work Environment, Job Satisfaction and Work Productivity.